2019
DOI: 10.26434/chemrxiv.7723226.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure, anion, and solvent effects on cation response in ESI-MS

Abstract: <p>The abundance of an ion in an electrospray ionization mass spectrum is dependent on many factors beyond just solution concentration. Even in cases where the ions are permanently charged and do not rely on protonation or other chemical processes to acquire the necessary charge, factors such as cation structure, molecular weight, solvent, and the identity of the anion can perturb results. Screening of a variety of combinations of cation, anion and solvent provided insight into some of the more important… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Many factors impact the quantitative determination of analyte concentrations via ESI MS. Ionization efficiency, desolvation, and detector response depend on the analyte molar mass and molecular shape along with the nature of the solvent and counterion. 44 Herein, the ESI MS samples from catalytic polymerization reactions were prepared identically and comparisons were made between the relative ion counts of 5 vs 6 observed in the same sample. Therefore, the solvent and anion differences are unlikely to impact the accuracy of these results.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Many factors impact the quantitative determination of analyte concentrations via ESI MS. Ionization efficiency, desolvation, and detector response depend on the analyte molar mass and molecular shape along with the nature of the solvent and counterion. 44 Herein, the ESI MS samples from catalytic polymerization reactions were prepared identically and comparisons were made between the relative ion counts of 5 vs 6 observed in the same sample. Therefore, the solvent and anion differences are unlikely to impact the accuracy of these results.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…82 More recently, studies have shown differences in ionization efficiency for fixed-charge organic ions depending on their origin from protic or aprotic solvent systems. 94 Thus, a sound understanding of the effects of different solvent systems on the various ionization processes described here could allow the tailoring of cVSSI techniques for specific comparative and structural -omics analyses.…”
Section: ■ Results and Discussionmentioning
confidence: 97%